Adsorptive and Photocatalytic Dye Removal from Wastewater Using Metal-Organic Frameworks. Issue 5 (March 2020) - Wei, Fuhua; Ren, Qinhui; Yang, Lili; Wu, Liu; Jian, Qianqian; Liang, Zhao; Chen, Ding
Abstract: Trimesic acid in conjunction with microwave-assisted ball milling was used to produce Fe-based metal-organic frameworks (Fe-MOFs). Fe-MOFs were then used to eliminate organic dyes from aqueous solutions. Our results indicated Fe-MOFs eliminated nearly all Methylene Blue (MB) and Methyl Orange (MO). Within 120 min of Xe or natural light exposure, Fe-MOFs were able to remove 93.11% and 91.6%, respectively, of 10 mg/L MB in a 200 mL solution. Within 300 min of Xe or natural light exposure, Fe MOFs were able to remove 96.34% and 52.32%, respectively, of 5 mg/L MO from a 200 mL solution. Collectively, these results show that both dyes are suitable for use in the second kinetic model.